Enforcing the Right to Child Support in Unreligious Marriages: An Analysis of the Dualism of Islamic Jurisprudence and Indonesian Positive Law - Naufal Ghifari; Emha Hasan Aminullah Asyari (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Religiously valid but unregistered marriages raise serious issues regarding the fulfillment of children’s maintenance rights. This study aims to analyze a father’s maintenance obligations from a fiqh perspective, examine Indonesia’s positive law regulations, map the normative dualism between the two, and formulate a synchronization model as a foundation for strengthening the protection of maintenance rights for children born of unregistered marriages. The study employs a qualitative normative legal method using legislative, conceptual, and comparative approaches, along with literature review as a data collection technique. The findings reveal that Islamic jurisprudence mandates child support unconditionally based on the validity of lineage without requiring administrative registration, whereas positive law requires formal proof through documents or court rulings. Constitutional Court Decision No. 46/PUU-VIII/2010 represents a significant breakthrough by recognizing the civil relationship between a child and their biological father through scientific evidence such as DNA testing. Legal dualism lies in the dichotomy between substantive-theological validity in fiqh and administrative-formal validity in positive law. Synchronization through the integration of the maqashid syariah with Article 28B of the 1945 Constitution, as well as the utilization of the isbat nikah mechanism and the determination of a child’s lineage, constitutes a crucial solution to ensure the certainty and enforceability of a child’s right to maintenance.